Transcriptome Profiling of Mouse Corpus Callosum After Cerebral Hypoperfusion - Takase, Hajime; Hamanaka, Gen; Ohtomo, Ryo; Ishikawa, Hidehiro; Chung, Kelly K.; Mandeville, Emiri T.; Lok, Josephine; Fornage, Myriam; Herrup, Karl; Tse, Kai-Hei; Lo, Eng H.; Arai, Ken (Frontiers in Cell and Developmental Biology, 2021)
White matter damage caused by cerebral hypoperfusion is a major hallmark of subcortical ischemic vascular dementia (SIVD), which is the most common subtype of vascular cognitive impairment and dementia (VCID) syndrome. In an aging society, the number of SIVD patients is expected to increase; however, effective therapies have yet to be developed. To understand the pathological mechanisms, we analyzed the profiles of the cells of the corpus callosum after cerebral hypoperfusion in a preclinical SIVD model. We prepared cerebral hypoperfused mice by subjecting 2-month old male C57BL/6J mice to bilateral carotid artery stenosis (BCAS) operation. BCAS-hypoperfusion mice exhibited cognitive deficits at 4 weeks after cerebral hypoperfusion, assessed by novel object recognition test. RNA samples from the corpus callosum region of sham- or BCAS-operated mice were then processed using RNA sequencing. A gene set enrichment analysis using differentially expressed genes between sham and BCAS-operated mice showed activation of oligodendrogenesis pathways along with angiogenic responses. This database of transcriptomic profiles of BCAS-hypoperfusion mice will be useful for future studies to find a therapeutic target for SIVD.